Barchan Slipface Grainflows: Characteristics and Kinematics - Douglas J. Sherman; Pei Zhang; Jon Pelletier; Jean Ellis; Eugene Farrell; Bailiang Li (Geophysical Research Letters)
Abstract Gravity‐driven grainflows on aeolian dunes are important agents of sand transport on Earth and Mars but have been the focus of few field studies. We present results from the first comprehensive field study to evaluate hypotheses posed by previous studies: (a) grainflow frequency depends on the sand transport rate; (b) grainflow magnitude is independent of sand transport rate; and (c) grainflow speed depends on its area. A barchan slipface was monitored with a terrestrial laser scanner and video camera, with measurements of wind speed and sand transport rate. More than 1,600 grainflows were detected and measured. Key findings support the first hypothesis, refute the second hypothesis, and support the third hypothesis. We also found that grainflow speeds measured in laboratory studies are substantially slower than comparable examples measured in this field study, and the grainflow speed and area relationships found for field and laboratory data are significantly different.